Health education in the control of Aedes aegypti – from theory to practice (Research, Society and Development, 2021)
Epidemic outbreaks of dengue in Brazil have been increasingly frequent. In 2020, the COVID19 pandemic associated with dengue, zika and chikungunya cases exposed the finite capacity of the health system, which makes the dengue theme even more urgent. Every year we are warned about the importance of eliminating breeding grounds for the Aedes aegypti mosquito (Linnaeus, 1762), through educational campaigns on local media, on social networks, among others. Even so, the population's low adherence to measures aimed at mosquito control is perceived. From this scenario, in this work we seek to list the main reasons presented by some authors for this low population adherence, as well as to present the main solutions pointed out in the scientific literature. General guidelines were pointed out so that health and education professionals develop alternatives capable of integrating health and education, in addition to promoting greater population engagement with vector control practices.